Student M.M., Vуnar V.A., Golovchuk M.Ya., Zakiev V.I., Gvozdetsky V.M., Gushchak R.I. Evaluation of micromechanical heterogeneity of gas-thermal coatings by using the microindentation and local spectral analysis - Студент, М. М.; Винар, В. А.; Головчук, М. Я.; Закієв, В. І.; Гвоздецький, В. М.; Гущак, Р. І. (Problems of Tribology, 2018)
A heterogeneous electric arc coating consisting of matrix phase Feγ lamellas and complex oxides of iron and chromium are formed as a result of electric arc spraying of powdered wire PD280X21SCGMP. The content of chromium in the coating lamellae varies from 16.4 to 20.3 wt. % with a typical content of 20.23 wt. % It is shown that the distribution of micromechanical characteristics in heterogeneous electric arc coatings depends on the nature, size and location of their structural components. In particular, chromium oxides contribute to the growth of microhardness, the modulus of elasticity and stresses of the second kind, and iron oxides reduce these characteristics. Wear resistance and the mechanism of coatings destruction is determined by structural parameters, their microheterogeneity and micromechanical characteristics.